KEDUDUKAN BANK DALAM PEMBERIAN BANK GARANSI - Novi Pujayanti, Putu; Bagiastra, I Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 05, Juli 2014)
Bank Guarantee is a product of the services offered by the Bank to its customers. Bank Guarantee is a type of guarantee, which is acting as the guarantor Bank. To obtain a guarantee from a Bank, then the Bank Guarantee issuance requires various requirements. These requirements have been stipulated in the Board of Directors of Bank Indonesia. 23/7/UKU Date March 18, 1991 regarding the granting of a Bank Guarantee by requiring that the issuance of Bank Guarantee , the Bank shall comply with the requirements specified. Writing this journal aims to determine how the position of the bank in granting the Bank Guarantee. Bank Guarantee, Bank serves as the guarantor of the Customer. Capacity as a guarantor in contrast to the position of guarantor in general. Here it can be deduced Position Bank in the Bank Guarantee is as guarantor and willing to fulfill the obligations of the Customer in the event of default. In writing this paper the authors use the method of normative and legal research with the formulation of the problem, namely the Position Bank in granting the Bank Guarantee.
Keywords: Position, Bank Guarantee, Customer